Trichome diversity studies in selected species of Sida - Ashwathy, G.; Krishnakumar, K. (Current Botany, 2020)
Sida (Family: Malvaceae) belongs to the genus of flowering plants that possess high medicinal value and is used traditionally in almost all parts of the world. There were about 18 species reported from the state of Kerala (India). Among these, some are with taxonomic controversies. Hence micro-morphological characters of leaves such as trichomes can be used as a taxonomic tool for the identification of plants. Their type, presence, absence and distribution are important diagnostic characters in plant identification and plant taxonomy. Plant samples were collected from different localities of Kerala. Foliar epidermal studies were carried out in order to identify the diversity and distribution of trichomes in the selected species of Sida viz., S. acuta, S. alnifolia, S. beddomei, S. cordata, S. cordifolia, S. fryxelli, S. ravii, S. rhombifolia and S. rhomboidea. Six types of trichomes were identified; they were stellate, conical, forked, capitate (short stalked), uniseriate multicellular and peltate. Stellate trichomes were observed in all the species. Conical trichomes were observed in S. beddomei, S cordata and S. fryxelli. Forked trichome was observed in S. acuta, S. cordata, S. cordifolia, S. ravii, S. rhombifolia and S. rhomboidea. Capitate (short stalked) trichomes were observed in S. acuta, S. alnifolia, S. rhombifolia and S. rhomboidea. Uniseriate multicellular trichomes were observed in S. cordifolia, S. fryxelli and S. ravii. Peltate trichomes are observed in all species except S. beddomei, S. cordifolia and S. fryxelli. However, these species could be easily distinguished by their conical trichomes. A bracketed dichotomous key was prepared for the identification of the species considered for the study.